GTF2I mutation in thymomas: independence from racial-ethnic backgrounds : an Indian/German comparative study - Jain, Deepali; Guleria, Prerna; Singh, Varsha; Parshad, Rajinder; Kumar, Sunil; Gaiser, Timo; Kurz, Katrin; Ott, German; Porubský, Štefan; Preissler, Gerhard; Sauer, Christian; Schölch, Sebastian; et al. (Pathology & oncology research, 2021)
Thymomas are the most frequent adult mediastinal cancers. Their etiology is unknown and their pathogenesis poorly understood. Racial, ethnic and environmental factors influence tumorigenesis in many cancers, but their role in thymomas remains unclear to date. In this study that included pretreatment thymoma cases from India and Germany (n= 37 and n=77, respectively) we compared i) the prevalence of the thymoma-specific chromosome 7 c.74146970T>A mutation of the GTF2I gene in type A and AB thymomas; ii) epidemiological features; and iii) the frequency of myasthenia gravis (MG). Due to a known predominance of GTF2I mutation in A and AB histotypes, we included only a marginal number of type B thymomas as a control group in both cohorts. While the distribution of histological types between the cohorts was similar(p=0.1622), Indian patients were strikingly younger (p<0.0001; median age 50 vs. 65 years) and showed significantly lower tumour stage (Masaoka-Koga stage I) at primary diagnosis (p=0.0005) than the German patients. In patients with known MG status (n=17 in Indian and n=25 in German cohort), a clear trend towards more frequent MG was observed in the Indian group (p= 0.0504; 48% vs 82%). The prevalence of the GTF2I mutation (analysed in n=34 Indian and n=77 German patients) was identical in the two cohorts. We conclude that racial-ethnic and environmental factors do not significantly influence the most common molecular feature of thymomas but may have an impact on the timing of clinical presentation.
Gesehen am 27.10.2021